Penggunaan Metode Analytic Hierarchy Process dalam Pengambilan Keputusan Penentuan Prioritas Program Kerja Dompet Dhuafa Yogyakarta - Djoko Wijono; Idham Ibty (Telaah Bisnis, 2016)
Abstract Manager always faced to make a choice from various alternatives. Here the necessary prioritization and test the consistency of the choices that have been made. In complex situations, decision-making is not influenced by one factor alone but is multifactorial and includes various levels and interests. The analytic hierarchy process (AHP) is a structured technique for organizing and analyzing complex decisions, based on mathematics and psychology. It was developed by Thomas L. Saaty in the 1970s and has been extensively studied and refined since then. The AHP helps decision makers find one that best suits their goal and their understanding of the problem. It provides a comprehensive and rational framework for structuring a decision problem, for representing and quantifying its elements, for relating those elements to overall goals, and for evaluating alternative solutions. In this study, AHP used for decission making in Dhompet Dhuafa planning programs. First we decompose their decision problem into a hierarchy of more easily comprehended sub-problems, The elements of the hierarchy can relate to any aspect of the decision problem. The AHP converts these evaluations to numerical values that can be processed and compared over the entire range of the problem. This study use metodhologies: brain storming discuss, indepth interview, and collect secondary data. Find Dhompet Dhuafa solution problems by AHP.The good point of this study is showed how to use AHP for decision making.